Outcome and status of postcardiac arrest care in Korea: results from the Korean Hypothermia Network prospective registry - Soo Hyun Kim; Kyu Nam Park; Chun Song Youn; Minjung Kathy Chae; Won Young Kim; Byung Kook Lee; Dong Hoon Lee; Tae Chang Jang; Jae Hoon Lee; Yoon Hee Choi; Je Sung You; In Soo Cho; et al. (Clinical and Experimental Emergency Medicine, 2020)
Objective High-quality intensive care, including targeted temperature management (TTM) for patients with postcardiac arrest syndrome, is a key element for improving outcomes after out-of-hospital cardiac arrest (OHCA). We aimed to assess the status of postcardiac arrest syndrome care, including TTM and 6-month survival with neurologically favorable outcomes, after adult OHCA patients were treated with TTM, using data from the Korean Hypothermia Network prospective registry. Methods We used the Korean Hypothermia Network prospective registry, a web-based multicenter registry that includes data from 22 participating hospitals throughout the Republic of Korea. Adult comatose OHCA survivors treated with TTM between October 2015 and December 2018 were included. The primary outcome was neurological outcome at 6 months. Results Of the 1,354 registered OHCA survivors treated with TTM, 550 (40.6%) survived 6 months, and 413 (30.5%) had good neurological outcomes. We identified 839 (62.0%) patients with preClinsumed cardiac etiology. A total of 937 (69.2%) collapses were witnessed, shockable rhythms were demonstrated in 482 (35.6%) patients, and 421 (31.1%) patients arrived at the emergency department with prehospital return of spontaneous circulation. The most common target temperature was 33°C, and the most common target duration was 24 hours. Conclusion The survival and good neurologic outcome rates of this prospective registry show great improvements compared with those of an earlier registry. While the optimal target temperature and duration are still unknown, the most common target temperature was 33°C, and the most common target duration was 24 hours.